2001
DOI: 10.1016/s0893-133x(01)00224-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olanzapine on Functional Responses from Sensitized D1-Dopamine Receptors in Rats with Neonatal Dopamine Loss

Abstract: (Breese et al. 1985a,b). For example, neonate-lesioned animals have increased locomotion following treatment with SKF-38393, a D 1 -DA receptor agonist, at doses that have minimal impact on control rats (Breese et al. 1985a,b). Repeated treatment with D 1 -DA agonists can lead to extremely high rates of activity in lesioned rats, and this "priming" effect can still be observed 6 months after the chronic drug treatment (Breese et al. 1985b;Criswell et al. 1989b). Supersensitivity of D 1 -DA receptors in neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This hypothesis is consistent with behavioral models of LNS, such as 6-OHDA-lesioned rats, which appear to self-injure in response to an increase in dopaminergic production [Breese et al, 1984[Breese et al, , 2005. Animal studies using dopamine antagonists were able to attenuate self-injury in multiple animal models of self-harm, including 6-OHDA-lesioned rats and unilateral ventromedial tegmental lesions in monkey models [Goldstein et al, 1986;Duncan et al, 1987;Criswell et al, 1989;Allen et al, 1998;Moy et al, 2001Moy et al, , 2004. Further, postmortem brains of LNS patients show increases in dopamine receptors [Saito et al, 1999], and HPRT-deficient mice are hypersensitive to dopamine-releasing agents [Jinnah et al, 1991[Jinnah et al, , 1992.…”
Section: Dopaminesupporting
confidence: 60%
“…This hypothesis is consistent with behavioral models of LNS, such as 6-OHDA-lesioned rats, which appear to self-injure in response to an increase in dopaminergic production [Breese et al, 1984[Breese et al, , 2005. Animal studies using dopamine antagonists were able to attenuate self-injury in multiple animal models of self-harm, including 6-OHDA-lesioned rats and unilateral ventromedial tegmental lesions in monkey models [Goldstein et al, 1986;Duncan et al, 1987;Criswell et al, 1989;Allen et al, 1998;Moy et al, 2001Moy et al, , 2004. Further, postmortem brains of LNS patients show increases in dopamine receptors [Saito et al, 1999], and HPRT-deficient mice are hypersensitive to dopamine-releasing agents [Jinnah et al, 1991[Jinnah et al, , 1992.…”
Section: Dopaminesupporting
confidence: 60%
“…We have recently reported that a dose of 5 mg/kg of olanzapine can only partially block similar locomotor rates induced by SKF-38393 in lesioned rats, while a full antagonism was observed at 10 mg/kg olanzapine (Moy et al 2001). The greater potency of olanzapine against PCP-stimulatory effects, in comparison to similar levels of activity induced by SKF-38393, suggests a differential mechanism of action against the NMDA antagonist than against the D 1 -DA agonist.…”
Section: Discussionmentioning
confidence: 90%
“…We chose olanzapine (OLZ) at doses of 1.0, 3.0 and 5.0 mg/kg because these are the commonly used doses in many behavioral studies of this drug (Kapur et al, 2003; Li et al, 2010; Moy et al, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Our previous work shows that both acute and chronic olanzapine treatments disrupt active components of maternal behavior (e.g., pup retrieval, pup licking and nest building) (Li et al, 2005). However, in that study, a relatively high dose of olanzapine (7.5 mg/kg, sc) was used, thus it is still not clear whether olanzapine at much lower doses that are commonly used in the behavioral studies of antipsychotic drugs (1.0, 3.0 or 5.0 mg/kg (Kapur et al, 2003; Li et al, 2010; Moy et al, 2001) would also disrupt maternal behavior. Additionally, little is known about the neural basis of this effect of olanzapine.…”
Section: Introductionmentioning
confidence: 99%